Effects of nanoemulsion and essential oil from the leaves of Ocotea elegans against Dysdercus peruvianus (Research, Society and Development, 2020)
The Dysdercus peruvianus Guérin-Méneville is commonly known as the cotton stainer bug. In this study, it was evaluated the insecticide activity and mode of action of the essential oil from leaves of Ocotea elegans Mez and its nanoemulsion against D. peruvianus. Leaves of O. elegans were extracted by hydrodistillation. The essential oil obtained was analyzed by gas chromatography coupled with electron impact mass spectrometry and flame ionization detector. The essential oil toxicity measured by lethal dose 50 (LD50) and survival rate of insects were recorded. Lastly, an assay was carried out to assess the inhibition of the enzyme acetylcholinesterase to determine a possible mechanism of action of insecticidal activity. The sesquiterpene sesquirosefuran was the major compound detected and corresponds to 92% of the components of the essential oil. The nanoemulsion more stable showed hydrophilic lipophilic balance (HLB 11.74), droplet size 92±1.80 nm, and polydispersity index (PDI of 0.215±0.015). After the topical application of the O. elegans essential oil, significant decreases in the survival of D. peruvianus occurred in a dose-response manner with LD50 = 162.18 μg and the survival rate of the nanoemulsion in D. peruvianus was 10.0±5.47, a better value than in pure essential oil. The acetylcholinesterase inhibition presented inhibition concentration (IC50 = 1.37mg/mL) and mixed type of inhibition. This indicates that the essential oil of leaves from O. elegans and its nanoemulsion are promising candidates for use in integrated pest management programs.